Unveiling economic barriers to cultural consumption in Chile: insights from SHAP analysis and predictive modeling - Valdés-Elizalde, Sixto; Mendoza-Llanos, Rodolfo; Molinillo-Jiménez, Sebastián; Campos, Pedro G. (Emerald, 2025)
Purpose This study aims to explore how economic, subjective, and cultural capital factors impact cultural consumption decisions in Chile, using data from the last National Survey of Cultural Participation in Chile. Design/methodology/approach Using advanced machine learning techniques, such as the LightGBM predictive model and SHapley Additive exPlanations (SHAP) analysis, we investigate how age, gender, educational level and access barriers, such as economic limitations and lack of time, influence the diversity and frequency of cultural consumption. Findings Hours dedicated to work and study affect cultural consumption differently according to gender, age and educational level, which should be considered in cultural inclusion policies. Additionally, we find that childhood cultural participation has a more pronounced positive impact on individuals with lower educational levels, supporting the importance of promoting access to culture from an early age to balance long-term differences in cultural consumption. Originality/value These findings contribute both theoretically and methodologically to the understanding of the various factors influencing cultural consumption and their interrelations. They recommend a review of cultural policies toward a more inclusive and adaptive approach to promote participation across all sectors of society, considering observations from a middle-income country such as Chile.
Barreras económicas al consumo cultural en Chile: análisis SHAP y modelos predictivos
Keywords: Marketíng; Industria cultural - Consumo - Chile; Aprendizaje automático (Inteligencia artificial); Cultural consumption; Machine learning; Predictive modeling; Consumption patterns; Cultural capital; Consumption barriers